Understanding the legality of Waqf Muaqqat: a Shariah perspective - Mohamad, Nor Asiah; Abd Razzaq, Isa (IIUM GWC, 2021)
It is clear that there is no specific text in the Quran or in Prophetic traditions, which disallow temporary Waqf. It is based on the ijtihad of the jurists from every Mazhab. This can be seen whereby there is some jurists in every Mazhab who explicitly or implicitly propose to the idea of temporary Waqf although their views are not the certified view in their Mazhab like Abu Yusuf from the Hanafis, An-Nawawi from the Shafies and Al-Mawardi from the Hanbalis. Since Waqf is a type of Sadaqah or specifically Sadaqah jaariyah (continuous charitable act), then it can be in the temporary or perpetual form. From the hadith of Ibn Umar, it can be understood that a Waqf property cannot be sold, or revoked during the period of Waqf. However, it does not prohibit temporary Waqf. This study investigates further Shariah position of Waqf Muaqqat with the objective to make it an acceptable Waqf practice and becomes one of the main product of Islamic Social Finance